Removal of pharmaceutical active compounds by constructed wetland systems - a sustainable phytoremediation technique? - Machado, Ana Isabel de Oliveira (2022)
Doutoramento em Restauro e Gestão Fluviais - Instituto Superior de Agronomia. Universidade de Lisboa